2005
DOI: 10.1016/j.bbmt.2004.12.334
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T-cell ability to exert immunodomination correlates with T-cell receptor: Epitope association rate

Abstract: When presented alone, H7 a and HY antigens elicit CD8 T-cell responses of similar amplitude, but H7 a totally abrogates the response to HY when both antigens are presented on the same antigen-presenting cell. We found that H7a- and HY-specific T-cell precursors had similar frequencies in nonimmune mice and expressed similar levels of CD5. The H7a -specific CD8 T-cell repertoire harvested at the time of primary response showed highly restricted T-cell receptor (TCR) diversity. Furthermore, T cells specific for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…We reported that H7 a -and HY-specific T cell precursors have similar frequencies in nonimmune mice, and that H7 a -specific CD8 T cells harvested at the time of primary response show highly restricted TCR diversity (23). Thus, the immunodominant status of H7 a is not a question of T cell precursor frequency or TCR diversity.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…We reported that H7 a -and HY-specific T cell precursors have similar frequencies in nonimmune mice, and that H7 a -specific CD8 T cells harvested at the time of primary response show highly restricted TCR diversity (23). Thus, the immunodominant status of H7 a is not a question of T cell precursor frequency or TCR diversity.…”
Section: Discussionmentioning
confidence: 79%
“…4A). Because the frequencies of anti-H7 a and anti-HY T cell precursors in the preimmune repertoire are similar (23), anti-H7 a T cells underwent more extensive expansion than anti-HY T cells. The salient finding though was the lack of synchronicity between expansion of the two T cell populations.…”
Section: Time-sequential Evaluation Of Anti-h7 a And Anti-hy T Cell Dmentioning
confidence: 99%
See 3 more Smart Citations